A alma vestida: estudo sobre a cestaria paumari - Menendez, Larissa Lacerda (2011)
The object of the research is the basketry of indigenous people Paumari, who lives in the region of Purus river, in Amazon, Brazil. This work explains how basketry´s confection is related to cosmogonic myths and the spiritual world. We investigate the meaning of these objects in cosmology, in the feminine ritual of initiation and how its meaning changed for paumari people. Our hypothesis is the basketry express deep symbols of mythology and imaginary . We use diferents techniques of research, as interviews, participant comment and myth analysis. Eliade (1963), Godelier (2001), Ribeiro (1995) and Ricoeur (2007) are authors who inspire the writing of this work. This thesis also presents a significant sample of patterns of paumari basketry and analyses on mythology, imaginary and the artistic production of this people